Women involvement in dry fish value chain approaches towards sustainable livelihood - Rabbanee, Fazlul Kabir; Yasmin, Sanoara; Haque, A. K. M. Ahasanul (New South Wales Research Centre Australia (NSWRCA)., 2012)
Coastal fisherwomen of Bangladesh are marginalized yet they play a significant role in different levels of dry fish marketing chain. This study covers seven different villages of Cox’s bazaar districts. A total of 280 women fishers among - 140 fisherwomen and 140 women workers, were selected for the study. The paper applies different aspects of DFID Sustainable livelihood model in the study areas to learn the livelihood pattern of sample respondents and explores to what extent the respondents have access to these basic livelihood assets like physical, natural, financial, social and human capital. It points out that the sample women are involved in different income generating activities like drying, sorting and grading, cleaning and salting. It focuses on respondents opinion regarding the factors that affect their ability to adopt different livelihood strategies like natural resource based strategy, non-natural resource based strategy and migration strategy. Finally it suggests some innovative marketing strategies to overcome the vulnerable situation faced by the fisherwomen and adopt better livelihood strategies and thus attain sustainable livelihood through better livelihood outcome.